Faktor-Faktor Yang Mempengaruhi Audit Delay: Solvabilitas, Pergantian Auditor Dan Opini Audit - Khairina Nur Shadrina; Cris Kuntadi (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Audit delay is the length of time for completing an audit carried out by an auditor, which is measured by the time difference between the date of the financial report and the date of the audit opinion in the financial report, and is one of the ratios to measure the company's ability to pay all obligations. This article reviews the factors that influence audit delay, namely solvency, auditor turnover and auditor opinion, a study of tax accounting literature. The purpose of writing this article is to build a hypothesis of the influence between variables to be used in further research. The results of this literature review article are: 1) solvency influences audit delay; 2) changing auditors affects audit delay; and 3) audit opinion has an effect on audit delay. .